2020
DOI: 10.1021/acs.jpclett.0c02144
|View full text |Cite
|
Sign up to set email alerts
|

Homochirality Originates from the Handedness of Helices

Abstract: Homochirality is a common feature of amino acids and carbohydrates, whose origin is still unknown. For example, 19 of 20 natural amino acids are L-chiral but deoxyribose sugars in DNA are always D-chiral. Meanwhile, right-handed helices are ubiquitous in nature. Are these two phenomena intrinsically correlated? Here, we propose that homochirality of amino acids and nucleotide sugars is originated from the handedness of helices. We show that right-handed 310-helix and -helix favor the L-chiral form for amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 36 publications
6
74
0
1
Order By: Relevance
“…3e and 3f, markedly improved correlations can be obtained. These results are in excellent agreement with our previous work about confirmational stability for other systems, 11,14,16,17,20 indicating that it is the electrostatic interaction that plays the dominant role with steric and exchange-correlation effects being minor yet indispensable. These results also suggest that even though those dimers with bulky alkane groups look special, they are indeed no exceptions.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…3e and 3f, markedly improved correlations can be obtained. These results are in excellent agreement with our previous work about confirmational stability for other systems, 11,14,16,17,20 indicating that it is the electrostatic interaction that plays the dominant role with steric and exchange-correlation effects being minor yet indispensable. These results also suggest that even though those dimers with bulky alkane groups look special, they are indeed no exceptions.…”
supporting
confidence: 92%
“…Patterns of the results emerged from these processes and analyses thereafter should provide us with clues about the origin of their stability. To analyze the results, we employ two schemes of the density-based total energy decomposition, [10][11][12][13][14] information-theoretic approach (ITA), [15][16][17][18] and natural bond orbital (NBO) 19 analyses, whose details are available elsewhere. 20 Figure 1 illustrates the profile of the C-C distance as a function of its flexible rotation from 0 to 360 with the step size of 5.…”
mentioning
confidence: 99%
“…Many different mechanisms have been proposed over the years to explain homochirality: the parity violation in weak nuclear interaction for molecular energy levels [3] or ionization by cosmic rays [4], or circularly polarized UV light from active star-forming regions [5]. Another study suggests that the helical structure of biological molecules could be at the root of homochirality, because homochiral structures built of chiral amino acids are thermodynamically more stable than heterochiral structures [6]. While some of these mechanisms could possibly explain an initial chiral bias, these effects are often too small to explain the near complete homochirality of life, which needs to be amplified and maintained dynamically [7].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, based on the model results for proteins and DNA to attribute the origin of homochirality, we proposed the Principle of Chirality Hierarchy, 5 which states that the propensity of lower dimension chirality is dictated by that of the higher dimension chirality.…”
mentioning
confidence: 99%
“…We have shown that righthanded -helix and 310-helix structures in proteins both favor the L-chiral form of amino acids, whereas deoxyribose sugars in right-handed DNA helical structures prefer the D-chiral form instead. 5 We also identified the existence of strong cooperativity effect, [5][6][7] which is dominated by the favorable electrostatic interaction in the homochiral conformation through the analysis of total energy partition 11,12 and information-theoretic approach. 13,14 In this work, we confirm the validity of the Principle of Chirality Hierarchy in an another axial chirality system, a left-handed three-blade propeller molecule (Scheme 1).…”
mentioning
confidence: 99%